Internalization of Educators' Role in Strengthening Students' Character Amidst Social Media Onslaught - Armedi, Rama; ’Izza, Aminatul Fattachil; Dilapanga, Raihan Retriansyah; Apriansyah, Apriansyah (Universitas of Muhammadiyah Makassar, 2025)
The rise of moral degradation among students due to uncontrolled exposure to social media has become a critical challenge in the world of education. This study aims to identify the role of educators in instilling character education to students who experience moral degradation due to technological advances followed by the onslaught of social media. This research was conducted qualitatively using a library research approach by identifying the role, relationship, and impact of social media on the character of students. The results explain that the moral degradation that occurs in students due to the onslaught of social media can be overcome by educators by internalizing the concept of character education in Yusuf Qardhawi's thoughts, namely Rabaniyah, Insaniyah, Syumul, Al-Wasathiyah, and Al Jam'u Baina Ats Tsabat wa Al Murunnah. This research is still very relevant in overcoming moral degradation in the era of social media onslaught with the approach of Yusuf Qardhawi's character education concept.